Pengaturan Eksplorasi dan Eksploitasi Tambang Minyak Menurut Unclos 1982 - Dieska, Nikolaus Giusti Priyageng; Michael, Tomy (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Indonesia’s marine resources include vast reserves of oil, gas, minerals and coal. The concession of the importance of the sea which is rich in natural reserves and a source of foreign exchange for the state has been strengthened by an international statement through the Convention on the Law of the Sea passed by the United Nations called UNCLOS 1982. Under the 1982 Convention on the Law of the Sea or UNCLOS, coastal states have the exclusivity of the seabed of their continental shelf to explore and exploit the country’s foreign exchange, and automatically acquire rights to the ecosystem or foreign exchange found there. The intention of this research is to understand the continental shelf regulations related to petroleum exploration and exploitation based on the 1982 UNCLOS international regulations. This type of research uses a prescriptive normative legal research method, using a statutory approach and a conceptual approach. Primary and secondary legal sources are used through inventory and literature research. Provisions regarding Indonesia’s continental shelf are contained in Law No. 1 of 1973 concerning the Indonesian Continental Shelf, but in Law No. 4 of 2009 concerning Mining and Coal Mining, as amended by Law No. 3 of 2020, and Law No. 32 of 2014 concerning the Law of the Sea concerning Seabed Mining. There are no specific provisions on seabed mining. Indonesia should consider amending Law No. 1 of 1973, particularly with regard to seabed mining regulations, and updating its marine resources law to bring it in line with international standards. Legal harmonization is needed to establish a unified legal framework for marine resource development.